CURRENT CHALLENGES IN THE DEVELOPMENT AND FORMULATION OF AMORPHOUS SOLIDS - Kumar, Gannu Praveen; Kumar, Bakka Sravan (Indonesian Journal of Pharmacy, 2012)
Interest  in  amorphous  pharmaceutical  systems  is  steadily growing  over  the  last  10  years.   The  amorphous  state  is  critical  in determining  the  solid  state,  physical  and  chemical  properties  of many pharmaceutical dosage forms. The main reason of the growing interest  toward  amorphous  materials  is  the  need  to  improve  the bioavailability  of  drugs  with  poor  aqueous  solubility.  Many  drugs exist in crystalline solid form due to reasons of stability and ease of handling during the various stages of drug development. Conversion of  the  crystalline  to  amorphous  form  may  occur  during  various pharmaceutical  processes.   This  could  change  the  dissolution  rate and  transport  characteristics  of  the  drug.  The  current  focus  of research  in  this  area  is  to  understand  the  origins  of  amorphous forms.  The  various  thermodynamic  phenomena  such  as  glass transition,  fragility,  molecular  mobility,  devitrification  kinetics, molecular  level  chemical  interactions,  solubility  and  stability  are critically  discussed.  The  aim  of  this  review  is  to  understand  the recent  development  in  the  area  of  amorphous  state  and  to  address the  current  challenges  faced  by  pharmaceutical  formulation  and process  development  scientists  and  thus  is  mandatory  to  anticipate future developments.Key words:  Crystalline solids, amorphous forms, characterization, stabilization.